Associations of clinical features of functional bowel disorders with gut microbiota characteristics in adolescents: A pilot study - A. I. Romanitsa; U. M. Nemchenko; A. V. Pogodina; E. V. Grigorova; N. L. Belkova; N. M. Voropayeva; E. A. Grigoryeva; M. V. Savelkayeva; L. V. Rychkova (Acta Biomedica Scientifica, 2021)
Background. Obesity is a multifactorial disease that is one of the important public health problems in the 21st century. Functional bowel disorders in obese children and adolescents are one of the most common pathologies of the digestive tract. The aim: to characterize the bacteriological composition of the colon microbiota in obese adolescents and identify its associations with the clinical manifestations of functional bowel disorders.Materials and methods. The study included 20 adolescents aged 11–17 years. Stool consistency was assessed using the Bristol Stool Scale. The study of biological material was carried out using standard bacteriological methods. To assess the strength of the relationship between the nominal variables, Cramer’s V test was used.Results. It has been shown that in adolescents with obesity and functional bowel disorders, there is a decrease in the number of representatives of bifidoflora, an increase in the microbial density of Escherichia coli with altered enzymatic properties and an excessive growth of potentially pathogenic enterobacteria. In obese adolescents with functional bowel disorders, abdominal pain associated with the act of defecation is associated with the presence of enterobacteria and E. coli with altered enzymatic properties. Rare bowel movements are associated with an increased abundance of Enterococcus spp. and the presence of opportunistic Enterobacteriaceae microorganisms. Frequent bowel movements are associated with the presence of E. coli with altered enzymatic properties and Clostridium spp. In the presence of loose stool, Clostridium spp. is present; unstable stool (alternation of hard and liquid stools in one patient) is associated with a decrease in the number of lactobacilli and E. coli with normal enzymatic properties, the appearance of E. coli with altered enzymatic properties, opportunistic microorganisms of Enterobacteriaceae family and Clostridium spp. Conclusion. The relationship between the clinical symptoms of functional bowel disorders and changes in the composition of the gut microbiota in obese adolescents may be a justification for conducting in-depth studies aimed at finding early predictors of functional bowel diseases associated with obesity in the adult cohort.